Regulation of Inflammatory Response and the Production of Reactive Oxygen Species by a Functional Cooked Ham Reformulated with Natural Antioxidants in a Macrophage Immunity Model - Antonio Serrano; Gaspar Ros; Gema Nieto (MDPI AG, 2019)
Nowadays, more consumers demand healthier products. A way to offer such products is to functionalize them using health-promoting bioactive compounds. Meat and meat products are high in essential nutrients; however, their excessive consumption implies a high intake of other substances that, at levels above recommended uptake limits, have been linked to certain non-communicable chronic diseases. An effective way to reduce this danger is to reformulate meat products. In this study, natural botanical extracts rich in anti-inflammatory and antioxidant compounds were used to improve the health properties of a cooked ham with an optimal nutritional profile (i.e., low in fat and salt). The RAW 264.7 mouse cell line was used as an inflammatory model and was stimulated with Escherichia coli lipopolysaccharide to evaluate changes in inflammatory biomarkers such as tumour necrosis factor alpha, the interleukins (ILs) IL-1β and IL-6, nitric oxide and intracellular reactive oxygen species (ROS). The results showed that the use of natural extracts in optimized cooked ham significantly downregulated inflammatory markers and reduced the levels of intracellular ROS. Thus, the present study proposed a new functional cooked ham with potential health properties via anti-inflammatory and antioxidant in vitro activity.